2021
DOI: 10.1002/rcs.2297
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vessel detection methods for organ‐mounted robots

Abstract: Background: HeartLander is a tethered robot walker that utilizes suction to adhere to the beating heart. HeartLander can be used for minimally invasive administration of cardiac medications or ablation of tissue. In order to administer injections safely, HeartLander must avoid coronary vasculature.Methods: Doppler ultrasound signals were recorded using a custom-made cardiac phantom and used to classify different coronary vessel properties. The classification was performed by two machine learning algorithms, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Targets were located within 2 mm using the single equivalent moving dipole mapping (SEMDM) technique. Feasibility of ablation via needle insertion was assess in an artificial tissue model and ex vivo tissue and within 2 mm of the target depth 46 . Further studies showed that doppler ultrasound signals were successfully used to identify and avoid coronary vascular during cardiac interventions using the robotic device 47 .…”
Section: Future Epicardial Access and Mapping Techniques: Preclinical...mentioning
confidence: 99%
See 1 more Smart Citation
“…Targets were located within 2 mm using the single equivalent moving dipole mapping (SEMDM) technique. Feasibility of ablation via needle insertion was assess in an artificial tissue model and ex vivo tissue and within 2 mm of the target depth 46 . Further studies showed that doppler ultrasound signals were successfully used to identify and avoid coronary vascular during cardiac interventions using the robotic device 47 .…”
Section: Future Epicardial Access and Mapping Techniques: Preclinical...mentioning
confidence: 99%
“…Feasibility of ablation via needle insertion was assess in an artificial tissue model and ex vivo tissue and within 2 mm of the target depth. 46 Further studies showed that doppler ultrasound signals were successfully used to identify and avoid coronary vascular during cardiac interventions using the robotic device. 47 Robotic assisted percutaneous pericardial access has not yet been shown to be feasible.…”
Section: Robotic-assisted Epicardial Mapping and Ablationmentioning
confidence: 99%